An inside look at External Affairs during the Trudeau years : the memoirs of Mark MacGuigan - MacGuigan, Mark, 1931-1998 (University of Calgary Press, 2002)
A personal account of the Honourable Justice Mark MacGuigan's -- Canada's Secretary of State for External Affairs -- experiences with Canadian foreign policy under Pierre Elliott Trudeau between 1980-1982. A beautifully crafted memoir of MacGugian's political life during a tumultuous time of renewed East-West tensions, challenging American-Canadian relations, and regional conflict. MacGuigan chronicles the events in which he participated, offering personal insights into his motivations and reactions. The book surveys a wide range of bilateral and multilateral issues, weaves together an intriguing cast of national and international characters, and offers important insights into the making of foreign policy from a ministerial perspective.